Why Jessie Conrad Was Not a Professional Typist. - Fachard, Alexandre (Conradian)
The article focuses on author Jessie Conrad's typewriting skill and discusses the difference of her typewriting skill with a good one. Topics discussed include typewriters used by her, types of keyboards used and their efficiency such as dhiatensor keyboard and qwerty keyboard and errors in her typescripts. The author is of the view that she lacks formal training otherwise her typescripts would have met and have the standardised professional look.